Factors persuade individuals’ behavioral intention to opt for Islamic bank services: Malaysian depositors perspective - Allah Pitchay, Anwar; Mohd Thas Thaker, Mohamed Asmy (Beşiz Publications, 2016)
The sustainable development of Islamic banking services has motivated large numbers of depositors to choose Islamic bank services instead of the conventional bank. There are various factors that can persuade the depositors’ choice to choose Islamic bank. The present study examines the factors that persuade individuals’ behavioral intention to choose Islamic bank services. Hence, to achieve this objective, this study employs the theory of planned behavior (TPB) as the underlying theory to measure the factors that persuade the depositors’ behavioral intention to choose Islamic bank services. A total of 300 questionnaires is distributed to Malaysian Islamic bank depositors in Peninsular Malaysia. The data from the questionnaires are analysed using structural equation modeling (SEM). The result shows three variables predicted the behavioral intention, namely attitude (ATT), subjective norms (SN) and perceived behavioral control (PBC) of the depositors are found significant to persuade depositors’ behavioral intention to choose the Islamic bank services. Furthermore, the finding of the study also confirmed the relevant of using TPB to measure the depositors’ behavioral intention and this result is fruitful for the body of knowledge in the area of Islamic finance and also provides positive implication for the practitioners